Factors Influencing Industrial Agglomeration in Indonesia - Az Zaakiyyah, Hizbul Khootimah (Dinasti Publisher, 2024)
This study analyzes the factors affecting industrial agglomeration in Indonesia using panel data from 34 provinces during the 2012-2023 period. The analytical methods employed include Location Quotient (LQ) and panel data regression, with testing results indicating that the Fixed Effect model is the most appropriate. The findings reveal that economic growth and investment have a negative and significant impact on industrial agglomeration, while the Human Development Index (HDI) shows a negative but insignificant effect. On the other hand, population size has a positive and significant influence on agglomeration.